Fragmented Society: A Qualitative Study on Social Cohesion in the Kurdistan Region-Iraq - Irwani, Muslih (Humanities Journal of University of Zakho, 2020)
Having accepted the claim that there is something as Kurdistan Region society, I argue that society, even in its homogenic form, is not safe from disagreement and conflict at internal level. With this approach towards the concept of society, this research investigates the principles and issues of social cohesion in the Kurdistan Region. It explores the extent to which the grievances and injustice among all the segments of society, including ethno-religious minorities and at inter-communal (between cities) level, have confronted the Kurdistan Region’s society with further segregation and fragmentation.